A random walk down Wall Street : the time-tested strategy for successful investing - Malkiel, Burton Gordon (New York : W.W. Norton & Co., 2011)
An informative guide to financial investment discusses the current high-tech boom, explains how to maximize gains and minimize losses, and examines a broad spectrum of financial opportunities, from mutual funds to real estate to gold.
Includes index.
Edition statement from jacket.
Keywords: Investments; Stocks; Random walks (Mathematics)